(3dZI GdMhGQ ai GdNWGH GdbUUi GdbQBfi (B: s (3OQGSI CSdhHjI JOGhdjI (B: (3GdShQ GdecjI fehPLG (B/ s - (3aGWeI YHOGdZaGQ YHOGdMGaX CHh WGdHs; (3eMeO MSf YHOGdYRjR (B: s ((3GdbGgQI (B: s (3aGWeI YHOGdZaGQ YHOGdMGaX CHh WGdH (B: s, 2021)
(3LGAJ gPg GdOQGSI JMJ YfhGf(B: "(3dZI GdpMhGpQ ai GdpNWGpH GdnbnUUi GdbQBfi(B: (3OQGSI CSdhHjI JOGhdjI(B: (3GdShQ GdecqjI fehPkLG(B": (3h bO GJNPJ gPg GdOQGSI ef pbUU GdCfHjGA ` eMd GdOQGSI ` GdeJaQbI ai ShQ cKjQI ef GdbQBf bUI hGMOkI ecJedI(B: (3aQCJ CMOGKgG eJQGHWI(B: (3h eTGgOgG eJUdI(B: (3h cGf GdMhGQ gh GdYfUQ GdQFjS GdPi SGYO Ydi gPG GdJQGHW(B: (3h Pdc GdGJUGd(B: (3acGf GdcTa Yf OhQg ai HfGA cd bUI(B: (3h eYQaI GdZQV efg h GdgOa GdeQLh ef hQGFg(B: (3h GSJbQGA Cge eG JJejR Hg dZJg ef SeGJ CSdhHjI h JOGhdjI; gh eG JOhQ Mhndg eMGhQ gPg GdOQGSI(B. (3Cge GdfJGFL GdJWHjbjI GdJi Je GdJhUd EdjgG(B: (3gjef GdMhGQ ai GdbUU ` eMd GdOQGSI ` Ydi HfjI GdbUI(B: (3h bO LGA CZdHg ai UhQI MhGQ NGQLi ZjQ eHGTQ JYOOJ CWQGag(B: (3HjfeG enqKdJ GdefGLGI ` Hjf HWd GdbUI h QHg ` h GdehfhdhL eSGMI bdjdI efg(B. (3SGQ YQV GdbUU GdCQHYI hab efgL eMOO JeKdJ bhGYOg ai HOA GdbUI HYQV JegjmO dgG bHd GdONhd ai CMOGKgG(B: (3h GNJjGQ YQV GdeTGgO ai cd bUI HfGA Ydi CgejI Jdc GdeTGgO ai GSJNdGU GdYHQI h GdYXI efgG(B: (3h dPG GNJdaJ GdbUU GdCQHYI ai eTgO GdHOGjI ai cd efgG(B: (3h GNJUGU cd ShQI HYQV GdeTgO Ch GdeTGgO ef GdbUI HeG jJhGab eY ehVhYgG h GdZQV GdPi ef CLdg fRdJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI OGQ GdYdhe (B- (3bSe Yde GddZI h GdOQGSGJ GdSGejI h GdTQbjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJOGhdjIs; (3GdNWGH GdaUUi GdbQBfis; (3dZI GdMhGQs